Pengembangan LKS Berbasis Virtual Laboratory Melalui ICT pada Materi Besaran dan Vektor Kelas X SMA - Fitrah Ayu; Masril Masril; Yenni Darvina; Hidayati Hidayati (PILLAR OF PHYSICS EDUCATION, 2018)
This research aims to determine the feasibility or properness of student worksheet based on virtual laboratory through ICT in studying quantity and vector among student in tenth grade of senior high school. In order to reach this goal, the R&D research is held which consist of: potential problem, data collection, product design, design validation, and product testing  or product trial. Data are analyzed by using technique of statistical graph. The object in this research is virtual laboratory based-student worksheet through ICT. The result of data analysis show that : the average validity test is 90 in valid category,  the average practicality test of teacher is 86 in practical category, and the average practicality test of student is 83 in practical category. With those results, the virtual laboratory based-student worksheet through ICT valued as proper to be used during the learning process of quantity and vector for the tenth grade student in senior high school.